2013
DOI: 10.1093/oep/gpt016
|View full text |Cite
|
Sign up to set email alerts
|

The drivers of happiness inequality: suggestions for promoting social cohesion

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 41 publications
5
75
2
Order By: Relevance
“…Should we then conclude that the change in happiness inequality is totally independent of income, as suggested by Stevenson and Wolfers (2008b), Dutta and Foster (2011) and Becchetti et al (2011)? We answer by running a RIF regression of the standard deviation of 9 See also Layard et al (2010) for the United States.…”
Section: The Role Of Income Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Should we then conclude that the change in happiness inequality is totally independent of income, as suggested by Stevenson and Wolfers (2008b), Dutta and Foster (2011) and Becchetti et al (2011)? We answer by running a RIF regression of the standard deviation of 9 See also Layard et al (2010) for the United States.…”
Section: The Role Of Income Inequalitymentioning
confidence: 99%
“…This includes Stevenson and Wolfers (2008b), Ovaska and Takashima (2010), Dutta and Foster (2011) and Becchetti et al (2011). Stevenson and Wolfers (2008b) and Dutta and Foster (2011) (Stevenson and Wolfers, 2008b, p.S34).…”
Section: Existing Literaturementioning
confidence: 99%
“…While it is possible that individuals measure life satisfaction in different latent scales, empirical work using vignettes (Beegle et al 2009;Clark et al 2012a and references therein) has found little evidence of reporting bias, in practice-this has also been corroborated using different approaches in recent work by Oswald and Wu (2009) and Oswald and De Neve (2012). Grounded on this evidence, the existing applied work on inequality in life satisfaction (Stevenson and Wolfers 2008;Becchetti et al 2011;Clark et al 2012a) also relies on this type of (uncorrected) measures. 25 For simplicity, this approach is also followed here.…”
Section: Latent Types Stochastic Dominance Conditions and Inequalitymentioning
confidence: 99%
“…Starting from the mid1990s, the evolution has either been described as trendless fluctuation (Clark et al 2016) or, less persuasively, as showing a slight increase in inequality (Becchetti et al 2013). What seems undisputed is that the 1990s saw a break in the downward trend towards less inequality in subjective well-being.…”
Section: The Link Between Economic Inequality and Life Satisfactionmentioning
confidence: 99%